2023
DOI: 10.1177/03635465231166708
|View full text |Cite
|
Sign up to set email alerts
|

Results of Endoscopic Labral Repair With Concomitant Gluteus Medius and/or Minimus Repair Compared With Outcomes of Labral Repair Alone: A Matched Comparative Cohort Analysis at Minimum 2-Year Follow-up

Abstract: Background: There is a paucity of information available to clinicians on outcomes of patients undergoing endoscopic surgery for labral repairs and femoroacetabular impingement syndrome with simultaneous repair of the gluteus medius and/or minimus muscles. Purpose: To determine whether patients with labral tears and concomitant gluteal pathology who undergo simultaneous endoscopic labral and gluteus medius and/or minimus repair experience similar outcomes to patients with isolated labral tears who undergo endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…After matching, there were no differences in these demographic characteristics or postoperative outcomes between the 2 groups. Similar to the findings of Horner et al, 13 who found successful results for patients with simultaneous labral and gluteal repairs compared with those undergoing isolated labral repairs, the present study highlights similarly successful outcomes of patients with gluteal pathology who undergo concomitant intra-articular intervention for FAIS and labral tear along with gluteal tendon repair when compared with a well-matched cohort undergoing isolated gluteal repair.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…After matching, there were no differences in these demographic characteristics or postoperative outcomes between the 2 groups. Similar to the findings of Horner et al, 13 who found successful results for patients with simultaneous labral and gluteal repairs compared with those undergoing isolated labral repairs, the present study highlights similarly successful outcomes of patients with gluteal pathology who undergo concomitant intra-articular intervention for FAIS and labral tear along with gluteal tendon repair when compared with a well-matched cohort undergoing isolated gluteal repair.…”
Section: Discussionsupporting
confidence: 89%
“…With a focus on gluteal tendon repair rather than labral treatment, the present study is the first to compare outcomes between patients who underwent concomitant endoscopic gluteus medius/minimus repair and arthroscopic hip labral repair and correction of FAIS versus those who underwent isolated endoscopic gluteus medius/minimus repair. The combined findings of the present study and the studies by Meghpara et al 19,20,21 and Horner et al 13 provide strong evidence that patients achieve excellent short-term outcomes even in overlapping gluteal, labral, and FAIS pathology. Based on these data, one can conclude that, in appropriately indicated patients, performing combined endoscopic gluteus medius/minimus and arthroscopic hip labral repair and correction of FAIS should not be expected to affect outcomes relative to either procedure alone.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations